THE VALUE OF CLINICAL AND LABORATORY PHENOTYPE IN PREDICTING THE COURSE OF COW’S MILK ALLERGY - E. E. Varlamov; A. N. Pampura (Вопросы современной педиатрии)
The prognosis of allergy to cow's milk protein allows to determine the length of elimination diet, and the timing of repeated prick screening for its expansion. Aim: to identify clinical and laboratory phenotype of patients with persistent cow's milk allergy. Patients and methods: the study included 52 children with allergy to cow's milk protein aged from 3 months to 5 years. The criterion for the development of tolerance to cow's milk was negative result of open oral provocation test with cow's milk. Results: tolerance to cow's milk occurred in 15 of 52 (28,8%) patients. Tolerance was achieved in 12 months in 10 children (19%), in 24 months — in 3 children (5,8%), in 36 months — in 1 patient (1,9%) and in 60 months — in 1 child (1,9%). In patients with persistent cow’s milk allergy the concentration of specific IgE to cow's milk protein was increased (p = 0,006) compared to a group of children who develop tolerance. Also in this group clinical course of AD (p = 0,01), sensitization to allergens of grasses (p = 0,006), sensitization to inhalant allergens (p = 0,04) and the presence of asthma (p = 0,037) were significantly more severe. Conclusions: in assessing the likelihood of development of tolerance to cow's milk protein it is necessary to consider not only the degree of sensitization to cow's milk protein, but also the severity of atopic dermatitis, the presence of asthma, sensitization to other allergens such as alimentary and inhalant ones. In patients with persistent allergy to the cow's milk protein development of asthma can be expected with high probability, which causes necessity of the providing of asthma prophylaxis in this group of patients.